Handbook of Halophytes 2020
DOI: 10.1007/978-3-030-17854-3_93-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Salt-Affected Soils Using Halophytes

Abstract: Increases in environmental pollution along with the increase of rapid population growth have now resulted in significant reduction in the agricultural areas and seriously threatened the proposed crop production. Salinization of lands, in particular, has become a major environmental problem and has been considered as one of the most significant issues to be tackled in arid or semi-arid regions of the world. Salinity not only reduces the agricultural crop production but also negatively affects the physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It is certain that the current arable land is far less sufficient for crop production. A solution to expand crop production is to use halophytic plants to remediate soil salinity and convert the soils to cultivable land (Karakas et al, 2020;Munir et al, 2022). Thus, an in-depth understanding of halophytic plant tolerance to salt stress would enable us to better use this group of plants for remediation of saline soils.…”
Section: Discussionmentioning
confidence: 99%
“…It is certain that the current arable land is far less sufficient for crop production. A solution to expand crop production is to use halophytic plants to remediate soil salinity and convert the soils to cultivable land (Karakas et al, 2020;Munir et al, 2022). Thus, an in-depth understanding of halophytic plant tolerance to salt stress would enable us to better use this group of plants for remediation of saline soils.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also made for S. soda plants by Karakas [51] who suggested that the improvement of tomato plants via companion plants under salt stress (1.3 and 6.5 dS m −1 ) was achieved with the synthesis of substances used for fruit development instead of building up substances for mechanisms of stress tolerance. It is important to note that synthesizing stress metabolites and antioxidant enzymes is quite costly for plants to cope with abiotic or biotic stress factors [17]. Instead of generating crop plants that can combat stress factors, the strategy that involves removing stress factors would be much appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Portulaca oleracea L. (purslane) (which is a member of Portulacaceae), is a drought-and salt-tolerant annual plant. The plant is a promising crop species in saline-alkali soils [16,17]. Moreover, P. oleracea could effectively absorb salts from soil media to remediate saline-alkali soils [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is sold as sea vegetable and salad crop at relatively high prices [ 27 ]. Salsola komarovii and S. soda are also used for soil salt and heavy-metal phytoremediaton [ 28 , 29 , 30 ], and in intercropping systems to increase the performance of glicophyte species [ 31 , 32 , 33 ]. Studies on the nutraceutical properties of Salsola spp.…”
Section: Introductionmentioning
confidence: 99%